Zhulavska O. O. Quantity analysis of the actualization of the commonsense notion “terrorism” in the modern English newspaper discourse - Zhulavska O. O. (Philological Treatises, 2020)
The article deals with the quantity analysis of the actualization of the commonsense notion TERRORISM in the modern English newspaper discourse. It brings to light the commonsense notion features of highly-probable and low-probable implication which are established on the basis of statistic calculations. It also defines typical and non-typical members of the action slot of the commonsense notion TERRORISM.